Обгрунтування перспективних напрямів розвитку альтернативних джерел енергії - Куруцова, Е.С. (Економічні інновації, 2015)
Визначено економічні, економіко-екологічні та соціальні збитки від аварії атомної електростанції в Японії та розвиток атомної енергетики в розвинених країнах світу. Проаналізовано розвиток відновлюваних джерел енергії в країнах ЄС та в Україні. Визначено передумови розвитку сонячної енергетики в Україні та основні інструменти її впровадження. Determined the urgency of the problem with regard to the provisions of the agreement with the EU aimed to develop and promote renewable energy on the principle of economic feasibility and environmental protection, given the structure of the energy sector of Ukraine, dynamics of production and the needs of society in the recovery, cost-effective source of energy which consider man-made each type of production and given the benefits of generating electricity from solar energy.